Effect of far-infrared radiation therapy on von Willebrand factor in patients with chronic kidney disease - Yen, Cheng-Chieh; Hsu, Po-Chao; Lin, Chih-Ching; Chen, Szu-Chia; Hsiao, Chih-Yen; Hwang, Shang-Jyh (Frontiers in Medicine, 2023)
Background Hemostatic abnormality has contributed to vascular access thrombosis in patients with chronic kidney disease (CKD). Previous studies have demonstrated that far-infrared radiation (FIR) therapy can maintain the patency and maturity of arteriovenous fistulas of patients undergoing hemodialysis (HD). However, prolonged access bleeding is observed once FIR is conducted at the end of dialysis. FIR can block the binding of platelet and von Willebrand factor (vWF), a predictor of hemostatic abnormality and vascular access thrombosis. However, clinical studies exploring FIR and vWF are sparse. Methods We recruited 20 HD patients, 21 CKD patients, and 20 controls to examine the alteration of vWF and a disintegrin and metalloproteinase with thrombospondin type 1 repeats 13 (ADAMTS13) following a single 40-min session of FIR therapy. In addition, the alteration of these factors in the HD group was examined following a 40-min FIR session thrice a week for 3 months. Results A decreasing trend in the vWF activity-antigen ratio of participants in all groups following a single FIR session was observed. In addition, the ratio in the HD group was significantly lower following 3 months of FIR therapy. The subgroup analysis revealed a consistent trend and multiple regression analysis showed that participants not taking hydroxymethylglutaryl-coenzyme A reductase inhibitor, diabetes mellitus, and higher hemoglobin levels were the significant factors. The alteration of the vWF activity-antigen ratio correlated moderately to that of ADAMTS13 antigen and activity. Conclusion FIR may alter the ratio of ultra-large vWF multimers through ADAMTS13, contributing to inhibiting platelet-endothelium interactions of CKD patients.